Anemia in severe heart failure patients: does it predict prognosis? - Abebe, Tamrat Befekadu (BMC Cardiovasc Disord, 2017)
BACKGROUND: Anemia is highly prevalent in heart failure (HF) patients. However, the prevalence, clinical impact and prognostic factor of anemia in heart failure patients is widely varies. The aim of this study was to evaluate the prevalence of anemia in patients with HF, to compare baseline clinical characteristic and outcomes of severe HF patients with and without anemia admitted to Gondar University Referral Hospital (GURH), Gondar, Ethiopia. METHOD: A retrospective cohort study was conducted and we assessed medical records of heart failure patients who were admitted Gondar University Referral Hospital in the period between December 02, 2010 and November 30, 2016. Kaplan Meier curve was used to analyze the survival status and log rank test was used to compare the curves. Multivariate Cox regression was used to analyze independent predictors of mortality in all HF patients. P value less than 0.05 was considered statistically significant. RESULT: Three hundred and seventy patients participated in the study. The prevalence of anemia in the study cohorts was 41.90% and majority of the participants were females (64.59%). There was a significant difference in the level of hemoglobin, creatinine, and sodium among anemic and non-anemic patients. Anemic patients with HF tend to take angiotensin converting enzyme inhibitors (ACEI) less frequently. Kaplan Meier survival curves and Log rank test (P = 0.042) showed a significant difference in the prognosis of HF patients with anemia and non – anemic. More significant difference was observed (Log rank test, P = 0.001) in the study participants based on hemoglobin level. Furthermore, multivariate Cox regression showed: advanced age, levels of lower sodium and higher creatinine, and absences of medications like ACEI and Spironolactone independently predicted overall mortality. CONCLUSION: HF patients with anemia tend to be older age, had lower hemoglobin and sodium level and higher creatinine value. Moreover, there was a significant difference in the prognosis between study cohorts, as anemic pateints tend to have a worse survival status . Even though, anemia is a significant risk marker, it is not an independent predictor of mortality in the current study.